MANAJEMEN ORGANISASI DAN PENGORGANISASIAN DALAM PERSPEKTIF AL-QUR’AN DAN HADITH - Fathor Rachman (LP2M IAI Miftahul Ulum Pamekasan, 2015)
Organization and organizing are the two things interconnected, if the organization is like a container, the organizing is an organism which makes it live in a dynamic organization. Organizing is the second step in the management of the organization after planning. Good planning will not run perfectly, without no one to run and move it, without cleared the job and who will do it. That is the essence of the organizing. Good organizing will be produces the right organization, from the work system, structure, resources, and other aspects. This study will discuss in depth the organization examined from the al-Qurân and Hadith perspective..This study used a concept-analytical methods combined with a thematic approach. The data were collected through the al-Qurân Hadith are so many mentioned the importance of organizing and structuring the organization it self known by organizing in management. The results of the study show: in the al-Qur'an, Allah has shown a very clear in setting of the human life, including the creation of all on earth and the sky. Even them a in substances in the organizing containing composing tasks and its distribution, structure formation and selection of the appropriate resources mentioned in the al-Qurân and Hadith. This is the al-Qur'an giving guidance to the people, especially the manager (leader) of an organization